Sliding bearings for hydropower applications : novel materials, surface texture and EALs - McCarthy, Donald (Luleå tekniska universitet, Maskinelement, 2008)
Hydropower, the utilisation of water as a means of driving machinery, has been used for many centuries. Today, the great power of water is being harnessed to generate as much as 20% of worldwide electricity. The requirement for reliable and efficient electricity generation needs to be matched by environmental awareness on the part of the industry. Work carried out during the course of my doctoral studies at Luleå University of Technology has been aimed at addressing these demands by investigating means of improving sliding bearing performance through the use of environmentally adapted lubricants and the employment of novel materials and surface texturing to reduce friction. The term "sliding bearing" refers to a type of bearing where two surfaces (usually the stationary bearing and a moving shaft) slide relative to one another with load distributed directly across the interface. In hydrodynamic bearings, a lubricant layer is built up in the contact region such that the two surfaces are completely separated. Examples of these are hydrodynamic journal and thrust bearings. These types of bearing are major components in many large machines, including hydroelectric turbines. Their safe operation relies on the maintaining of sufficient oil film thickness. As long as this condition is met, the bearing could continue to do its job indefinitely. This is particularly important during transient operating conditions (i.e. rapid changes in load or speed) when oil films can momentarily become extremely thin. Such conditions have been examined for a tilting-pad thrust bearing to assess impact on operation. More and more onerous demands are being placed on such bearings and their associated methods of lubrication, e.g. increased frequency of start/stop of hydroelectric turbines. This means that new solutions are required to maximise their operational performance. One such solution attracting current attention is the employment of surface texturing. The impact of surface texturing on the performance of a tilting-pad thrust ...